Out of Time : Desire in Atemporal Cinema - McGowan, Todd (Book collections on Project MUSE., 2011)
In Out of Time, Todd McGowan takes as his starting point the emergence of a temporal aesthetic in cinema that arose in response to the digital era. Linking developments in cinema to current debates within philosophy, McGowan claims that films that change the viewerAEs relation to time constitute a new cinematic mode: atemporal cinema. In atemporal cinema, formal distortions of time introduce spectators to an alternative way of experiencing existence in timeùor, more exactly, a way of experiencing existence out of time. McGowan draws on contemporary psychoanalysis, particularly Jacques Lacan, to.